A Very Simple Suture Technique for Correction of Primary Multiple Folds in Asian Eyelids. Issue 8 (29th November 2022) - Kim, Jeenam; Na, Youngsu; Jeong, Minkyoung; Jun, Dongkeun; Lee, Myungchul; Shin, Donghyeok; Kim, Soonheum; Jo, Dongin; Kim, Sooyoung; Choi, Hyungon
Abstract : Background: Upper blepharoplasty is 1 of the most popular cosmetic procedures in Asia. As people become older, they develop soft tissue atrophy and multiple folds due to a sunken upper eyelid. Furthermore, people with thin upper eyelid skin are more likely to develop multiple folds, even at a young age. The authors investigated the effectiveness of a transverse mattress suture technique to prevent recurrence during upper blepharoplasty in patients with primary multiple folds. Patients/Methods: Data on 656 patients with primary multiple folds who underwent upper blepharoplasty from March 2017 to January 2020 were retrospectively reviewed. The authors compared the operative time, patients' satisfaction, panel assessment, and complications according to whether the suture technique was used. Results: Among 656 patients, 228 were lost to follow-up or had incomplete data; therefore, the files of 428 patients were analyzed. In total, 199 patients did not undergo the suture technique, whereas 229 patients did. Statistically significant differences were found between the 2 groups in patients' satisfaction, aesthetic results, and recurrence. However, between-group difference was not significant in terms of symmetry or complications such as hematoma and swelling. Conclusions: People with thin upper eyelid skin or slightly protruding eyes are more likely to develop multiple folds at a young age, even in their teens or 20s. The authors performed a skin suture during upper blepharoplasty, and then performed a transverse mattress suture on the spots where multiple folds are expected. Patients who underwent the suture technique showed better aesthetic results and a significantly lower recurrence rate.